Approximate Solutions to Three-Point Boundary Value Problems with Two-Space Integral Condition for Parabolic Equations. (11th April 2012) - Niu, Jing; Lin, Yingzhen; Cui, Minggen
Abstract : We construct a novel reproducing kernel space and give the expression of reproducing kernel skillfully. Based on the orthogonal basis of the reproducing kernel space, an efficient algorithm is provided firstly to solve a three-point boundary value problem of parabolic equations with two-space integral condition. The exact solution of this problem can be expressed by the series form. The numerical method is supported by strong theories. The numerical experiment shows that the algorithm is simple and easy to implement by the common computer and software.